Conformable microfluidics and its application in wearable sensing - Lee, Benjamin Wen Long (Nanyang Technological University, 2023)
There are many conformable microfluidics and its application in wearable sensing. However, not many provides quick data analysis and ultilises a new type of sensor, nanobioreator holographic sensors. The research methods employed were experimenting with different types of materials for the sweat sensor and a collaboration with SIMTECH staff for the holographic sensors. The project identified that this concept is still far-reached but has the potential for more innovation. Through this project, the proof of concept between the microfluidics and the holographic sensor has worked. This means that further research and experimentation can be done to achieve the final product of a quick, at-home self-diagnosis for at-healthrisk patients.